Aplikasi Arsitektur Modern Pada Redesain Pasar Induk Tradisional Lambaro - Rudy Saputra (Universitas Syiah Kuala, 2020)
The trade sector is the most important thing in a district, especially the Lambaro Traditional Market which became the main driver of the economy in the area. But, the current condition of the market looks very chaotic, slum, dirty due to lack of maintenance, both in physical buildings and facilities, so that it’s necessary to do a redesign of the market in order to be able to compete with modern markets that are developing at this time.. Application of the theme for market redesignis